Strawberry cultivars with Fragaria orientalis Losinsk. in their pedigrees - A. A. Kharchenko; V. I. Belevtsova; I. G. Chukhina (Труды по прикладной ботанике, генетике и селекции)
Development of productive strawberry cultivars adapted to harsh winter conditions is an urgent task for plant breeders in Russia. The M. G. Safronov Yakut Scientific Research Institute of Agriculture has used wild strawberry forms combining several useful agronomic and biological traits, primarily the resistance to extreme environmental conditions, to achieve this objective. In the efforts to preserve the diversity of crop cultivars, the N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) has developed and is implementing a program to establish nomenclatural standards for domestic cultivars of vegetatively propagated crops. The results of the implementation of this program are presented. Nomenclatural standards for the strawberry cultivars ‘Alexandra’, ‘Pokrovskaya’, ‘Sadovospasskaya’, ‘Vladyka Zosima’ and ‘Bersenevskaya’, released by the M. G. Safronov Yakut Scientific Research Institute of Agriculture, have been formalized, registered in the VIR Herbarium Database, and placed for conservation in the Herbarium of Cultivated Plants of the World, Their Wild Relatives, and Weeds (WIR).